The term "reading" in the work of Abdul Malek Mortad - Bouali, Abderrahmane Abdellah (Al-Adab Journal, 2020)
The term "reading" is a basic term in modern and contemporary criticism, and has received great care by researchers in various fields of knowledge, for its importance and efficiency.The critics treated this term so specially that they placed him at the forefront.This research aims to reveal this term in the work of an active researcher, Abdul Malik Murtad, who was able through scientific research to make his name one of the active names in Arab criticism. Throughout our research we will pause for a long time on the term "reading" as seen by this researcher and used in his research.